Vietnam : Enhancing Enterprise Competitiveness and SME Linkages - World Bank Group (World Bank, Washington, DC, 2017)
The objective of this report is to inform the Government of Vietnam’s on-going efforts to enhance the competitiveness of the domestic private sector and to facilitate foreign direct investment (FDI) spillovers and linkages. This report is anchored in the government’s supporting industries (SI) policy framework that aims to upgrade the capabilities and technology of local enterprises to facilitate supplier linkages with FDI, as well as enable them to enter foreign markets. FDI’s spillover potential - the productivity gain resulting from the diffusion of knowledge and technology from foreign investors to local economy - is considered the most valuable input to growth and development. Creating linkages is not automatic, as various supply-side constraints and market failures often hinder the process. International experience and academic research has shown that while many countries have successfully attracted FDI, the record with capturing spillovers is mixed due to a variety of market failures. This report focuses on the operationalization of the FDI linkage development agenda in Vietnam. Building on the diagnostics established by the aforementioned studies, it reviews both international and domestic experiences, and offers recommendations to strengthen policies and programs to support enterprise competitiveness and linkages in Vietnam.